Impact of cellular manufacturing and lean production planning and control on production flow efficiency in a SME - A case study in the protective and security industry - ÍSAKSDÓTTIR, GUNNHILDUR JÓDÍS; REYNISDÓTTIR, STEFANÍA RUT (My University, 2016)
Today’s increasing global competition and customer requirements has had great impact on the manufacturing industry. In order to respond to this ever changing circumstances and sustaining a place on the market, many organizations have started following the lean production methodology. This is no exception for SMEs and due to their important role in modern economics there is a need to help them enhance their efficiency and competitiveness. Previous research has put a lot of focus on how the lean production methodology can be adopted and implementing into the large manufacturing enterprises but much less focus has been put on SMEs. Therefore, the purpose of this research was to get a deeper understanding of how cellular manufacturing and lean production planning and control impact production flow efficiency in a SME. A qualitative research strategy was mainly used with a single case study design. The case study was conducted within the protective and security industry, where the selected case was formed by a population of small Swedish corporation that was interested in lean production. The data collection consisted of interviews, observation, value stream mapping, time study, commonality study, benchmarking and secondary data. The results show that cellular layout impact the production flow by creating more standardized production steps that impacts the changeover time and the throughput time. Creates less waste within the production as all tools and material are positioned exactly where they need to be. It increases visuality of the production, increases teamwork and lastly helps to reveal hidden problems. The result also showed that lean production planning and control techniques, pull, takt time and heijunka, impacts the production flow. By introducing pull, the inventory control improves, in regards to having the right material at the right time. By having takt time the waste will be reduced. Using heijunka helps the production to become more stable by balancing the capacity in the production to the customer need. These techniques further help the production to become more predictable and therefore, reduce the bullwhip effect. The production will also become more visual in regards to what needs to be produced and lastly, the WIP will be reduced. Therefore, both cellular manufacturing and lean production planning and control impact the production flow efficiency in SME. This research is believed to be a valuable addition to the field of lean as it tries to address how SMEs can adopt cellular manufacturing and lean production planning and control techniques into their production. This research is also believed to be an addition to the literature of production flow efficiency as the results reveal that there is a strong connection between the production flow efficiency and the two areas studied in a SME production environment.
Keywords: Transport; Övrig industriell teknik och ekonomi; Transport; Other industrial engineering and economics